Water demand management strategies in fast-growing cities. The case of Arequipa, Perú. Issue 3 (4th May 2022) - Zapana-Churata, Luis; March, Hug; Sauri, David
ABSTRACT: Using a socioenvironmental perspective, this paper analyses strategies of water demand management (WDM) in Arequipa, Peru, and their perception by residents through a survey of six city districts (three in the core and three on the periphery) complemented with interviews with key stakeholders. The results show significant differences in WDM. Strategies to reduce demand through pricing are dominant. Domestic water-saving technologies are uncommon, and awareness campaigns are limited to periods of water stress. Despite differences in water access, improvements in water networks (leak repair, adequate water pressure and continuous supply) are the most demanded actions by residents.